Cancer predisposing syndromes in childhood and adolescence pose several challenges necessitating interdisciplinary care in dedicated programs - Kaffai, Stefanie; Angelova-Toshkin, Daniela; Weins, Andreas B.; Ickinger, Sonja; Steinke-Lange, Verena; Vollert, Kurt; Frühwald, Michael C.; Kuhlen, Michaela (Frontiers in Pediatrics, 2024)
Introduction Genetic disposition is a major etiologic factor in childhood cancer. More than 100 cancer predisposing syndromes (CPS) are known. Surveillance protocols seek to mitigate morbidity and mortality. To implement recommendations in patient care and to ascertain that the constant gain of knowledge forces its way into practice specific pediatric CPS programs were established. Patients and methods We retrospectively analyzed data on children, adolescents, and young adults referred to our pediatric CPS program between October 1, 2021, and March 31, 2023. Follow-up ended on December 31, 2023. Results We identified 67 patients (30 male, 36 female, 1 non-binary, median age 9.5 years). Thirty-five patients were referred for CPS surveillance, 32 for features suspicious of a CPS including café-au-lait macules (n = 10), overgrowth (n = 9), other specific symptoms (n = 4), cancer suspicious of a CPS (n = 6), and rare neoplasms (n = 3). CPS was confirmed by clinical criteria in 6 patients and genetic testing in 7 (of 13). In addition, 6 clinically unaffected at-risk relatives were identified carrying a cancer predisposing pathogenic variant. A total of 48 patients were eventually diagnosed with CPS, surveillance recommendations were on record for 45. Of those, 8 patients did not keep their appointments for various reasons. Surveillance revealed neoplasms (n = 2) and metachronous tumors (n = 4) by clinical (n = 2), radiological examination (n = 2), and endoscopy (n = 2). Psychosocial counselling was utilized by 16 (of 45; 35.6%) families. Conclusions The diverse pediatric CPSs pose several challenges necessitating interdisciplinary care in specified CPS programs. To ultimately improve outcome including psychosocial well-being joint clinical and research efforts are necessary.